(untitled) (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2023)
This case study explores the combined use of JavaScript, jQuery, and the AI-driven tool ChatGPT to efficiently extract data from HTML tables, specifically focusing on a website containing Middle Chinese and Old Chinese readings of characters. The study provides a step-by-step guide for accessing the website, utilizing browser developer tools, implementing JavaScript and jQuery code, and leveraging ChatGPT to refine the extraction process. By employing this methodology, the extraction of Chinese characters and their corresponding readings from an HTML table was automated, saving time and effort. The resulting data was then imported into a Google Sheets document for further analysis. This case study highlights the potential of AI-driven tools to enhance web development tasks and streamline data extraction processes, demonstrating their value for both technical and non-technical users.